The Role of Serum Calcium Levels in Pediatric Dyslipidemia: Are There Any? - Peng, Yaguang; Hu, Lixin; Nie, Xiaolu; Cai, Siyu; Yan, Ruohua; Liu, Yali; Cai, Yanying; Song, Wenqi; Peng, Xiaoxia (Frontiers in Pediatrics, 2021)
Background: No previous study explored the association between serum calcium levels and dyslipidemia in children. This study aims to explore this relationship in children, based on a multicenter cross-sectional study population in China. Methods: Cross-sectional data was derived from the Pediatric Reference Intervals in China (PRINCE) study conducted between 2017-2018 involving 5252 males and 5427 females, a mean age of 10.0 ± 4.6 years. Multivariable logistic regression models were applied to calculate odds ratios (ORs), with 95% confidence intervals (CIs), for dyslipidemia of each serum calcium level and albumin-corrected calcium levels, which were sorted into quartiles. The restricted cubic spline model was fitted for the dose-response analysis. An L-shaped dose-response relation between calcium levels and the probability of dyslipidemia was found after the adjustment for multiple potential confounding factors, p for nonlinear < 0.001. Results: Using the middle category of calcium level as the reference, multivariable-adjusted ORs and 95% CIs of the lowest and the highest quartile categories were 0.96 (0.82-1.12) and 1.29 (1.12-1.48) respectively for total serum calcium levels, while 1.06 (0.91-1.23) and 1.39 (1.21-1.60) for albumin corrected calcium levels. Conclusions: Individuals with higher level of serum calcium were at increased risks of dyslipidemia in a sample of a healthy Chinese pediatric population. The associations between serum calcium levels and dyslipidemia need to be explored in the future studies.